On-chip preparation of nanoscale contrast agents towards high-resolution ultrasound imaging. Issue 4 (22nd December 2015) - Peyman, Sally A.; McLaughlan, James R.; Abou-Saleh, Radwa H.; Marston, Gemma; Johnson, Benjamin R. G.; Freear, Steven; Coletta, P. Louise; Markham, Alexander F.; Evans, Stephen D.
Abstract : We present the first on-chip atomisation-like production of phase-change contrast agents at high concentrations towards high-resolution contrast imaging for diagnostic ultrasound. Abstract : Micron-sized lipid-stabilised bubbles of heavy gas have been utilised as contrast agents for diagnostic ultrasound (US) imaging for many years. Typically bubbles between 1 and 8 μm in diameter are produced to enhance imaging in US by scattering sound waves more efficiently than surrounding tissue. A potential area of interest for Contrast Enhanced Ultrasound (CEUS) are bubbles with diameters <1 μm or 'nanobubbles.' As bubble diameter decreases, ultrasonic resonant frequency increases, which could lead to an improvement in resolution for high-frequency imaging applications when using nanobubbles. In addition, current US contrast agents are limited by their size to the vasculature in vivo . However, molecular-targeted nanobubbles could penetrate into the extra-vascular space of cancerous tissue providing contrast in regions inaccessible to traditional microbubbles. This paper reports a new microfluidic method for the generation of sub-micron sized lipid stabilised particles containing perfluorocarbon (PFC). The nanoparticles are produced in a unique atomisation-like flow regime at high production rates, in excess of 10 6 particles per s and at high concentration, typically >10 11 particles per mL. The average particle diameter appears to be around 100–200 nm. These particles, suspected of being a mix of liquid and gaseous C4 F10 due to Laplace pressure, then phase convert into nanometer sized bubbles on the application of US. In vitro ultrasound characterisation from these nanoparticle populations showed strong backscattering compared to aqueous filled liposomes of a similar size. The nanoparticles were stable upon injection and gave excellent contrast enhancement when used for in vivo imaging, compared to microbubbles with an equivalent shell composition.